2011
DOI: 10.1063/1.3647898
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Study of dielectric relaxations of anhydrous trehalose and maltose glasses” [J. Chem. Phys. 134, 014508 (2011)]

Abstract: Dynamics of glass-forming liquids. III. Comparing the dielectric α-and β-relaxation of 1-propanol and -terphenyl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 10 publications
2
8
1
Order By: Relevance
“…It can be seen that the imaginary and the real components of the complex permittivity cross at some frequency f c which coincides perfectly with the maximum of loss of the relaxation process, labeled by Bhardwaj et al as the structural one. One can add that a similar situation was observed in the case of data presented by Kwon et al…”
Section: Resultssupporting
confidence: 86%
“…It can be seen that the imaginary and the real components of the complex permittivity cross at some frequency f c which coincides perfectly with the maximum of loss of the relaxation process, labeled by Bhardwaj et al as the structural one. One can add that a similar situation was observed in the case of data presented by Kwon et al…”
Section: Resultssupporting
confidence: 86%
“…Changes in temperature (T), pressure, chemical structure and purity have been studied by BDS by several authors revealing a strong impact of all four on the emerging dynamics. [23][24][25][26][27][28][29][30][31] Using FTIR Imamura et al 32 and Wolkers et al 33,34 found a remarkable sensitivity to the glass transition of the spectral positions of hydroxyl group vibrations. In the following we present the temperature dependence of fucose in a wide range around the glass transition temperature, T g , and time dependent (aging) measurements for T o T g .…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the relaxation times at 143 °C, they are 5.88 × 10 –6 s (De Gusseme) and 4.49 × 10 –7 s (Kaminski). These differences were difficult to observe in the earlier publication since the temperature scale was compressed to accommodate numerous relaxation profiles in one figure (Figure 1 in the paper by Kaminski et al). There are similar differences in the relaxation values reported by different groups for the two local relaxations as well (Figure 1 in the paper by Kaminski et al).…”
Section: Resultsmentioning
confidence: 81%
“…Recently, Kwon et al recognized the shoulder in the conductivity tail to be the α-relaxation peak and modeled it without dc conductivity removal . Kaminski et al argued that the relaxation peak, which Kwon et al labeled as the α-relaxation, originated from dc conductivity and the actual primary relaxation was mislabeled as the excess wing . However, in an effort to perform a careful comparison, we digitized the relevant plots from the literature and present all the data in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation